Entre a utopia e o mal-estar: reflexões psicanalíticas sobre os militantes do MST e seus dilemas - Domingues, Eliane (2011)
MST was officially founded in 1984 and is nowadays present at 23 states and the federal district. It involves nearly 1.5 million people and about 400 thousand are at camps. Its main aims, since the foundation, are: fighting for land, fighting for land reform, and fighting for a more fraternal and fair society (MST, 2009). Having passed more than 25 years of existence, many conquered their land, but land reform and the desired social transformations, ideals that move militants, are still far from achievement. Before this context, this research has asked: how do militants experience the distance between current society and the society they fight for, which is equal and fraternal to all? How do they experience the tension between living in a capitalist society supporting socialist values and ideals? How is tension between demanding and charges from collective (MST) and the ideals (social and psychic ambits) present at militants‟ everyday life? These questions were formulated from what the MST militants themselves present as being the dilemmas they face and they constitute as object of research of this thesis. The theoretical reference adopted was psychoanalysis and research methodology psychoanalytical intervention research. It was built on Freud‟s idea (2007/1927) that some classes, groups, and subjects pay more‟ sacrifice to live in the culture and developed the hypothesis that the militant, for not accepting this more‟ of sacrifice imposed by his class, ends up paying more‟ for his militant condition, what does not simply mean exchange this more‟ sacrifice for other, as new sacrifices are paid with a social place inside MST and with the possibility of a subject narcissistic revitalization, that is, they are paid with more‟ satisfaction enabled by ideals adhesion. In order to the ideals keep moving the subjects, it is necessary that between them and the current state of the subject or society always exist some distance. Something should always be missing so that the desire keeps flowing, but what misses to the subjects not be woeful, is to be based on a future project, some hope. This is what MST does: offer to subjects a future Project, a hope. Its militants afford the desire that moves them, but always bet on it, even if it costs them a pound of flesh